Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.3389/fimmu.2021.752003
|View full text |Cite
|
Sign up to set email alerts
|

Broadly-Neutralizing Antibodies Against Emerging SARS-CoV-2 Variants

Abstract: The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) variants have become a major concern in the containment of current pandemic. The variants, including B.1.1.7 (Alpha), B.1.351 (Beta), P1 (Gamma) and B.1.617.2 (Delta) have shown reduced sensitivity to monoclonal antibodies, plasma and/or sera obtained from convalescent patients and vaccinated individuals. Development of potent therapeutic monoclonal antibodies (mAbs) with broad neutralizing breadth have become a priority for alleviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
64
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 88 publications
(208 reference statements)
2
64
0
Order By: Relevance
“…Another study found that a naturally infected individual produced uncommon genetic and structural characteristics and showed potent neutralization against authentic SARS-CoV-2 viruses, including VOCs [32]. These results are consistent with other reports [33][34][35] and highlight the need for more epidemiological data about the contribution of previously exposed individuals with naturally-acquired immunity to herd immunity. Overall, these issues are scarcely considered in any statistical model.…”
Section: Discussionsupporting
confidence: 85%
“…Another study found that a naturally infected individual produced uncommon genetic and structural characteristics and showed potent neutralization against authentic SARS-CoV-2 viruses, including VOCs [32]. These results are consistent with other reports [33][34][35] and highlight the need for more epidemiological data about the contribution of previously exposed individuals with naturally-acquired immunity to herd immunity. Overall, these issues are scarcely considered in any statistical model.…”
Section: Discussionsupporting
confidence: 85%
“…Importantly, the gains in affinity observed for the engineered molecules translate into an increase in their potential to not only neutralize the interaction between RBD and the human ACE2, but also the entry of the SARS-CoV-2 virus into human cells. Unlike many class IV antibodies which often are weakly neutralizing, 40 our molecules demonstrate a strong capacity to neutralize the SARS-CoV-2 virus, with low EC50 in the ng/mL and picomolar range. Recently, rimteravimab, which is derived from VHH72 and incorporates a single substitution corresponding to S56A, has shown protection in mice and Syrian hamster animal models.…”
Section: Discussionmentioning
confidence: 78%
“…Importantly, the gains in affinity here observed for the engineered molecules translate into an increase in their potential to not only neutralize the interaction between RBD and the human ACE2 but also the entry of the SARS-CoV-2 virus into human cells. Unlike many class IV antibodies, which often are weakly neutralizing, 42 our molecules demonstrate a strong capacity to neutralize the SARS-CoV-2 virus, with low EC50 in the ng/mL and picomolar range. Recently, rimteravimab (XVR011), a bivalent nanobody-Fc molecule derived from VHH72 that incorporates a single substitution corresponding to S56A, has shown protection in mice and Syrian hamster animal models.…”
Section: Discussionmentioning
confidence: 81%